2020
DOI: 10.1002/term.3006
|View full text |Cite|
|
Sign up to set email alerts
|

Intratendon delivery of leukocyte‐rich platelet‐rich plasma at early stage promotes tendon repair in a rabbit Achilles tendinopathy model

Abstract: Tendinopathy is a great obstacle in clinical practice due to its poor regenerative capacity. The influence of different stages of tendinopathy on effects of leukocyte‐rich platelet‐rich plasma (Lr‐PRP) has not been elucidated. The aim of this study is to investigate the optimal time point for delivery of Lr‐PRP on tendinopathy. A tendinopathy model was established by local collagenase injection on the rabbit Achilles tendon. Then after collagenase induction, following treatments were applied randomly on the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 49 publications
(89 reference statements)
1
33
0
Order By: Relevance
“…Therefore, whether inflammation is beneficial for tendon healing depends on the different stages of tendon disorders. A previous study demonstrated that delivery of L-PRP at the early rather than the late stage promoted the repair of Achilles tendinopathy in rabbits and suggested that L-PRP may alleviate inflammation at the early stage, whereas L-PRP exerted a less prominent beneficial effect at the late stage of tendinopathy (23). This is consistent with the findings of Zhang et al (28), Zhou et al (35) and Jiang et al (38).…”
Section: Effects Of L-prp On Tendon Healing Based On Basic Studiessupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, whether inflammation is beneficial for tendon healing depends on the different stages of tendon disorders. A previous study demonstrated that delivery of L-PRP at the early rather than the late stage promoted the repair of Achilles tendinopathy in rabbits and suggested that L-PRP may alleviate inflammation at the early stage, whereas L-PRP exerted a less prominent beneficial effect at the late stage of tendinopathy (23). This is consistent with the findings of Zhang et al (28), Zhou et al (35) and Jiang et al (38).…”
Section: Effects Of L-prp On Tendon Healing Based On Basic Studiessupporting
confidence: 90%
“…Angiogenesis. A number of in vitro and animal studies have reported that administration of L-PRP significantly increased angiogenesis during the early phase of the tendon repair process (19)(20)(21)(22)(23)(24). It has been suggested that poor vascularity is a major factor limiting tendon healing capacity (25).…”
Section: Effects Of L-prp On Tendon Healing Based On Basic Studiesmentioning
confidence: 99%
See 3 more Smart Citations